43‐3: Laser Assisted LED for High Output Automotive DMD Headlight. Issue 1 (28th June 2021) - Li, Kenneth; Chang, Y.P.; Chen, Andy; Wang, Lion; Tsai, Stark
Abstract : Most of ADB headlight engines are designed using blue LED or laser light sources for the exciting the phosphor conversion layer producing white light output. The phosphor conversion layers have been fabricated by silicone‐based phosphor, glass‐based phosphor, ceramic‐based phosphor, and single crystal‐based phosphor. Among these different phosphor materials, the single crystal phosphor (SCP) exhibits excellent thermal stability, better conversion efficiency, and high transparency to yellow light, but the required high‐temperature fabrication process, has been an impediment for widespread commercial production. Recently, the issues of higher fabrication temperature of the SCP have been overcome by using a novel design of single crystal growth to produce SCP with higher yield and better uniformity. In this study, the ADB headlight consists of a well‐developed, high efficiency, automotive qualified white LED, a TI digit mirror device (DMD), a projection lens, and a Laser‐Assist™ LED system using two laser diodes and a SCP plate. The SCP plates are fabricated by Czochralski technology at the high temperature of 1, 940°C. Using the laser for the Laser‐Assist™ process, a 50% increase in the LED is obtained. This increase in output enables the increase in FOV and brightness of the ADB headlight, which results in significant improvement of the visibility and the illumination distance. The proposed advanced ADB headlight with ultra‐reliable SCP and Laser‐Assist™ LED system will become one of the most promising ADB headlight candidates for use in the next‐generation autonomous vehicle applications.